Effect of thioglycerol capping on morphology and structure of chemically deposited CdS:NaF,La films - Deshmukh, Kusumanjali; Mukherjee, Mimi; Bhushan, Shashi; Agrawal, R C (Recent Research in Science and Technology, 2012)
This paper reports the effect of thioglycerol as capping agent for synthesis of lanthanum (La) doped nanocrystalline CdS semiconducting films on the glass substrate by means of chemical bath deposition (CBD), with Cd(CH3COO)2 as Cadmium (Cd) ion source, and (NH2)2CS as sulphur (S) ion source. Long, rod like structures is observed in SEM micrographs of the films. XRD studies show the existence of both hexagonal and cubic phases. Increase in FWHM is observed for smaller particle due to nanocrystalline effect. UV-VIS absorption studies show shift of absorption edge towards lower wavelength side.